ANALISIS SIFAT KIMIA TEPUNG DAN PATI SORGUM DARI VARIETAS BIOGUMA DAN LOKAL DI PROVINSI NUSA TENGGARA TIMUR, INDONESIA - Adnan Nur Avif; Aptika Oktaviana TD (UIN AR-RANIRY, 2020)
Sorghum is a cereal that thrives in arid areas. In Indonesia, sorghum has been cultivated in several regions, but the quantity is still limited. The objective of this study was to determine the chemical properties of Bioguma sorghum developed by the Ministry of Agriculture where is grown in Nusa Tenggara Timur compared to local varieties of red sorghum. Sorghum flour and starch were analyzed for crude protein, water, ash, fat, and crudes fiber, starch and its components, and mineral profiles (calcium, iron, and zinc). Statistical analysis showed significant differences in nutrient composition in the flour and starch of Bioguma sorghum and red sorghum. The amylose content in flour affects the swelling and solubility of sorghum.